The Effect of Sit and Reach Test Exercise on Hamstring Muscle Flexibility of Persikoba Football Players - Maulidin, Ahmad Hanif; Pamungkas, Hari; Yusuf, Havid; Nidommuddin, Muhammad; Aofal, Reza (Jurnal Pendidikan Jasmani (JPJ), 2025)
The purpose of this study was to analyze the effect of Sit and Reach test-based training on the flexibility of Persikoba soccer players. Flexibility is an important component in athlete performance, especially in soccer, which requires agility, good range of motion, and injury prevention. This research method used an experimental method with a pre-test and post-test design. The subjects of the study were Persikoba soccer players selected by purposive sampling. Sit and Reach-based flexibility training was given 3 times a week for 2 months in a certain period, and data was measured before and after the intervention using the standard Sit and Reach test. The results showed that Sit and Reach-based training had a significant effect on increasing the flexibility of Persikoba soccer players. The average Sit and Reach value increased significantly after the training intervention compared to before the training.